2022
DOI: 10.3390/v14071351
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Itraconazole Is a Potent Inhibitor of Chikungunya Virus Replication

Abstract: Chikungunya virus (CHIKV) is the causative agent of chikungunya fever, a disabling disease that can cause long-term severe arthritis. Since the last large CHIKV outbreak in 2015, the reemergence of the virus represents a serious public health concern. The morbidity associated with viral infection emphasizes the need for the development of specific anti-CHIKV drugs. Herein, we describe the development and characterization of a CHIKV reporter replicon cell line and its use in replicon-based screenings. We tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…2c). According to previous results, the antimalarial MMV000008 (Chloroquine) [22] and the broad spectrum indirect antiviral agent MMV690621 (GSK-983) [19,23,24] presented potent anti CHIKV activity and high selectivity, with EC50 values in the low micromolar and nanomolar range, respectively (Fig. 3).…”
Section: Hits Confirmation: 4 New Anti-chikv Candidate Drugssupporting
confidence: 60%
See 3 more Smart Citations
“…2c). According to previous results, the antimalarial MMV000008 (Chloroquine) [22] and the broad spectrum indirect antiviral agent MMV690621 (GSK-983) [19,23,24] presented potent anti CHIKV activity and high selectivity, with EC50 values in the low micromolar and nanomolar range, respectively (Fig. 3).…”
Section: Hits Confirmation: 4 New Anti-chikv Candidate Drugssupporting
confidence: 60%
“…Accordingly, our screening approach successfully identified previously reported CHIKV antiviral compounds in the PRB and further expanded potentially active hits to compounds that presumably target steps in the replication cycle that involve the function of structural proteins. Among the compounds that resulted active in the primary and secondary screening, MMV690621 was previously reported to have anti-CHIKV activity in the subgenomic replicon-based assays reported by Policastro et al [19], and MMV000008 (Chloroquine) was previously shown to inhibit virus entry and release [22]. Overall, our approach using fFFU reduction of CHIKV-ZsGreen as a screening method effectively identified compounds active against CHIKV.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Itraconazole is a promiscuous anti-cancer and anti-fungal compound identified in different repurposing screenings as a broad-spectrum antiviral agent [ 95 , 96 , 97 ]. As mentioned in Section 2.2.3 , itraconazole interferes with enteroviral replication independently from its anti-fungal and anti-cancer activities and is inactive against 3A-resistant mutants, suggesting 3A as a potential target.…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%